(untitled) (Global Journal of Human-Social Science, 2012)
With the advent of globalisation the world has become a global village In other words traveling to other countries has become easy since the travel industry has facilitated economic growth world trade international investment and tourism This paper addresses the future of air travel due to the adoption of an open sky policy by some of the developing countries who are somehow forced to do so as other airlines become too competitive The first and foremost purpose of this dissertation is to assess the impacts and benefits of regulation and liberalisation on developing countries with a special consideration for the small island developing states SIDS Mauritius is a classic example of one such state that has favoured free enterprise for its economic development and has had to give up the quasi-monopoly of its flag carrier Moreover the purpose of this paper is to exhibit the benefits of an open sky policy for the government and the consumer Furthermore the paper also aims at explaining the potential threats that a flag carrier like may face with the advent of an open sky policy Another objective of this project has been to devise a policy theory that could help airlines of SIDS to develop further strategies within a framework where deregulation and liberalization are bound to become a necessity and inevitable development to reckon with